Sense of presence and learning satisfaction among students of different age groups in a 3-D virtual world - Rahman, M. H. A.; Eh Phon, Danakorn Nincarean; Utama, N. I.; Yahaya, N.; Halim, N. D. A.; Kasim, S. (Insight Society, 2019)
Virtual worlds are growing in popularity very quickly. This growing popularity of 3-dimensional (3-D) virtual worlds has drawn attention from educationists. Today, 3-dimensional (3-D) virtual worlds are exploited for online and virtual learning. Unlike the common online learning platforms, a virtual world environment closely resembles a 3-D video games environment. Thus the age of students might affect their sense of presence, interaction, and satisfaction in the said environment. Hence this study was conducted to investigate whether there are differences between students of different age groups on their sense of presence (place presence, social presence, and co-presence) and their learning satisfaction. The study was carried out for six weeks and involved 33 part-time diploma students with the use of interview and questionnaires as instruments. In this study, the researcher developed our own 3-D virtual world, known as ViEW, by using the Open Wonderland open source virtual world program. A nonparametric Mann-Whitney U analysis was applied to explore the differences between young and senior participants in terms of their sense of place presence, social presence, co-presence, and learning satisfaction. The results indicated significant differences between young and senior students in terms of place presence, co-presence, and learning satisfaction, but no differences were identified for social presence. These results might be in regard with the means of conducted the learning, which were in the forms of cooperative and synchronous learning by utilizing audio communication most of the time. Several recommendations for future research related to the study were also provided.